EXIT SURVEY SEBAGAI UPAYA MENINGKATKAN LAYANAN BANTUAN BELAJAR - Kristanti Ambar Puspitasari; Benny Agus Pribadi (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2015)
The satisfaction of the alumni reflects the quality of the college they graduated from. Those who were satisfied and proud of their alma mater can become marketing agents for their colleges. The alumni satisfaction with the student support services available for them during their study can be obtained by administering an exit survey. Exit surveys at the same time can also capture information about support services that have not been in accordance with the need for the students. By undertaking the exit survey, the management can also elicit information on services that haven’t meet the needs of the students. Continuous improvement of services is expected to increase the persistence rate of the students. This article aims to analyze the results of the exit surveys conducted at the university. The results of the analysis can be considered for the improvement of learning support services to students. Kepuasan alumni dapat mencerminkan kualitas dari suatu perguruan tinggi. Alumni yang merasa puas dan bangga terhadap almamaternya dapat menjadi agen pemasaran bagi perguruan tingginya. Kepuasan alumni terhadap layanan bantuan belajar yang disediakan bagi mereka selama studi dapat dijaring dengan metode exit survey. Exit survey sekaligus juga dapat menjaring informasi mengenai layanan bantuan belajar yang belum sesuai dengan kebutuhan selama menjadi mahasiswa. Perbaikan layanan kepada mahasiswa dapat meningkatkan tingkat kebertahanan mahasiswa pada perguruan tingginya. Artikel ini bertujuan untuk menganalisis hasil exit survey di Universitas Terbuka (UT). Hasil analisis dapat dijadikan bahan pertimbangan untuk peningkatan layanan bantuan belajar kepada mahasiswa.